Submerging a Biomimetic Metallo‐Receptor in Water for Molecular Recognition: Micellar Incorporation or Water Solubilization? A Case Study. Issue 68 (26th November 2018) - Collin, Solène; Parrot, Arnaud; Marcelis, Lionel; Brunetti, Emilio; Jabin, Ivan; Bruylants, Gilles; Bartik, Kristin; Reinaud, Olivia
Abstract: Molecular recognition in water is an important topic, but a challenging task due to the very competitive nature of the medium. The focus of this study is the comparison of two different strategies for the water solubilization of a biomimetic metallo‐receptor based on a poly(imidazole) resorcinarene core. The first relies on a new synthetic path for the introduction of hydrophilic substituents on the receptor, at a remote distance from the coordination site. The second involves the incorporation of the organosoluble metallo‐receptor into dodecylphosphocholine (DPC) micelles, which mimic the proteic surrounding of the active site of metallo‐enzymes. The resorcinarene ligand can be transferred into water through both strategies, in which it binds Zn II over a wide pH window. Quite surprisingly, very similar metal ion affinities, pH responses, and recognition properties were observed with both strategies. The systems behave as remarkable receptors for small organic anions in water at near‐physiological pH. These results show that, provided the biomimetic site is well structured and presents a recognition pocket, the micellar environment has very little impact on either metal ion binding or guest hosting. Hence, micellar incorporation represents an easy alternative to difficult synthetic work, even for the binding of charged species (metal cations or anions), which opens new perspectives for molecular recognition in water, whether for sensing, transport, or catalysis. Abstract : Molecular recognition in water : A well‐structured biomimetic core capable of Zn II coordination and anion hosting has been efficiently transferred into water through two strategies (see graphic), whereupon it retains its remarkable properties.